Kinetically inert transition metal complexes that reversibly bind to DNA. - Metcalfe, C; Thomas, J (2003)
Transition metal complexes that reversibly bind to DNA have been studied for almost 30 years. In the last few years a variety of new systems have been developed, employing a range of metal ions and ligand architectures. In many cases, high affinity binding and specific selectivities have been observed. These complexes display properties that make them attractive as probes of DNA structure and function, suggesting that they may find a rôle as prototypical tools for a spectrum of applications, from basic molecular biology to medicine. This review presents an overview of some of the structures and properties of such complexes.